Isomolar series methodology in sensory analysis of fish culinary products for HEALTHY-CAFE - Manoli, Tatiana; Nikitchina, Tatiana; Kameneva, Natalia; Barysheva, Yana; Deli, Viktoria (Technology audit and production reserves, 2023)
The object of research is the technology of fish products for HELTHY-CAFE with regulated histamine content for the development of health food diets for the population. One of the most problematic places in the technology of food products from raw materials of aquatic origin is microbiological spoilage and, as a result, the formation and accumulation of HisA, which in a certain amount causes a toxic effect. In the course of the study, the methods of isomolar series, sensory analysis, and the study of quality indicators were used. The methodology chosen in the work allows to determine the optimal ratio of hydrocolloids in the system for maximum complexation with histamine in the technology of fish culinary products in gelatin fillings with a harmonious sensory profile and adjustable histamine content. The obtained results of the conducted research allow to state that the proposed method of determining the optimal ratio of sodium alginate and low-esterified pectin substances contributes to the development of a gelatinous filling for fish culinary products in order to ensure the harmonious flavor of ready-made fish dishes and contributes to the expansion of the range of fish products for HELTHY-CAFE with functional and preventive properties. This is due to the fact that taking into account the modern trends in nutrition regarding the safety, functionality, palatability, and attractiveness of fish food products made it possible, based on the method of isomolar series and sensory analysis, to scientifically substantiate the optimal ratio of plant biopolymers, to form requirements for the texture of gelatin filling in fish technology culinary products. On the basis of previous experimental studies, it was shown that the accumulation of histamine occurs more actively in sea fish, which made it possible to substantiate the choice of raw materials for the production of fish culinary products. Taking into account the main global trends in the development of aquaculture, it is proposed to use crucian carp as a raw material, as the main object of aquaculture in Ukraine. The low activity of the peptide hydrolase complex of the muscle tissue of the carp, compared to sea fish, contributes to the formation of a harmonious aromatic profile of fish culinary products, which corresponds to consumer expectations, and the use of natural hydrocolloids of vegetable origin to form a gelatinous structure provides functional properties to the food product and allows controlling the histamine content.